G183(P) Clinical management of acute pain in paediatric sickle cell disease (SCD) following the nice guidance (CG143). (25th October 2020) - Huckerby, L; Clubb, R; Leigh, A
Abstract : Aims: To assess if children with SCD presenting to our District General Hospital with an acute painful episode are managed in line with NICE guidance. To compare our results with previous audits (2014 and 2016). To use feedback from the multi–disciplinary team (MDT) to develop sustainable interventions to ensure guidance is met. Methods: We performed a retrospective case note review (n=28) of medical notes. Primary data were collected from June-December 2018 and included all paediatric patients with SCD who presented in pain to the emergency department. Results: Our findings were presented to the MDT. Our local guideline was amended, with particular focus on the need to prescribe laxatives, anti-emetics and anti-pruritics to patients taking regular opioids, as well as timely pain relief. Feedback from the MDT, and reviewing interventions used by previous audits led us to amend induction for new doctors, emphasising the guideline and key audit findings. Conclusions: Clear improvements have been made from previous audits, however, despite this, there was a stark drop in our rates for offering analgesia within 30 minutes. This may reflect the challenges we face in providing rapid interventions in an ever-growing busy emergency department. Studies show that specialist care is superior over generalist care and improves outcomes (Bundy et al. 2016; Evensen et al. 2016). The Sickle Cell Society suggests a Specialist Haemoglobinopathy Team with links to local hospitals could support acute pain services, as well as an individualised care plan for each patient. This audit reinforces the importance of good acute care pathways and consideration should be given to alternative models of emergency care delivery.